Vibrational characteristics of piping system in air conditioning outdoor unit - Loh, S. K.; Faris, Waleed Fekry; Hamdi, M.; Chin, W. M. (Zhongguo Kexue Zazhishe, 2011)
The modal analysis of piping system in air conditioner (AC) outdoor unit is essential to investigate the vibration properties of the system. In view of the growing significance of numerical finite element (FE) model for vibration behaviour prediction, the AC piping elastic end support characterization has been explored. The axial and radial stiffness variables (k a , k r1, k r2) of the compressor-piping mounting are obtained and represented by dynamic stiffness of compressor grommet. They are obtained from dynamic load deflection test based on compressor operating condition such as excitation frequency and amplitude. The unknown stiffness variables of the other tube end (chassis-piping mounting) are determined by parameter fine tuning. An experimental modal analysis using impact hammer test has also been employed to determine the vibration properties such as natural frequencies, mode shapes and damping ratio of the piping structures. The modal parameters acquisition using SCADAS mobile acquisition system and LMS Impact Testing software is compared with the corresponding simulated modal properties using Abaqus. Most of the simulated natural frequencies achieve good correlation with the measured frequencies and it is reasonably a good prediction model to predict vibration behaviour of AC piping structures.